2021
DOI: 10.3390/vaccines9050511
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine: A Survey of Hesitancy in Patients with Celiac Disease

Abstract: (1) Background: COVID-19 vaccination campaigns offer the best hope of controlling the pandemic. However, the fast production of COVID-19 vaccines has caused concern among the general public regarding their safety and efficacy. In particular, patients with chronic illnesses, such as celiac disease (CD), may be more fearful. Information on vaccine hesitancy plays a pivotal role in the development of an efficient vaccination campaign. In our study, we aimed to evaluate COVID-19 vaccine hesitancy among Italian CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…However, only 11% of the participants took the vaccine in our study, which was significantly lower than the national average uptake (3). This acceptance was also significantly lower than the data of Italian patients living with inflammatory bowel disease (80.3%) (18) and celiac disease (74.8%) (19). On one hand, the acceptance in our study referred to the rate of patients who had already received the vaccine, which might be lower than the rate of willingness.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…However, only 11% of the participants took the vaccine in our study, which was significantly lower than the national average uptake (3). This acceptance was also significantly lower than the data of Italian patients living with inflammatory bowel disease (80.3%) (18) and celiac disease (74.8%) (19). On one hand, the acceptance in our study referred to the rate of patients who had already received the vaccine, which might be lower than the rate of willingness.…”
Section: Discussioncontrasting
confidence: 89%
“…In December 2019, coronavirus disease 2019 (COVID- 19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), broke out and led to a rapid worldwide pandemic. Up to the end of July 2021, COVID-19 had caused more than 192 million confirmed cases and over 4 million fatalities worldwide (1).…”
Section: Introductionmentioning
confidence: 99%
“…A survey done on students as representatives of the younger population confirmed that the majority of them would accept vaccination [122] in both Naples and Southern Italy. Some specific populations that were also included in surveys included people experiencing homelessness, out of which two-thirds of them expressed willingness to vaccinate [123] , while a high rate (74%) of willingness was also observed among celiac disease patients [124] . Finally, studies that assessed parents’/caregivers’ willingness report that English participants were less willing to vaccinate their children (48.2%) compared with Italian participants [125] , where more than 90% were willing to have their children take the recommended vaccine [126] .…”
Section: Resultsmentioning
confidence: 99%
“…Other determinants that most frequently led to vaccine confidence were found to be trust in vaccine safety (51.0% of participants who were willing to get vaccinated) and the fact that respondents had never had problems with vaccinations in the past (34.3%). Past adherence to vaccinations and, consequently, having experienced common adverse reactions and having observed vaccination safety firsthand are indeed considered to be contributing predisposing factors for vaccine confidence [ 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%